2006
DOI: 10.1002/jso.20529
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of silent gallstones in gallbladder cancer

Abstract: Silent (asymptomatic) gallstones are detected frequently with the widespread use of abdominal ultrasonography. The presence of gallstones is found strongly associated with gallbladder carcinoma. Studies on the natural history and most decision analysis studies do not favor prophylactic cholecystectomy for patients with silent gallstones. Gallbladder carcinoma is known to be highly aggressive and lethal disease with a poor outcome. It is rarely diagnosed early and only 10-30% patients are offered radical surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
(24 reference statements)
1
13
0
2
Order By: Relevance
“…Animal studies have shown dietary garlic and onions reduce diet-induced cholesterol gallstones [30], a well-established risk factor for gallbladder cancer [3, 31, 32, 33]. Evidence from our study supports this finding, as consumption of both garlic and onions was associated with a moderately decreased risk of gallbladder cancer.…”
Section: Discussionsupporting
confidence: 84%
“…Animal studies have shown dietary garlic and onions reduce diet-induced cholesterol gallstones [30], a well-established risk factor for gallbladder cancer [3, 31, 32, 33]. Evidence from our study supports this finding, as consumption of both garlic and onions was associated with a moderately decreased risk of gallbladder cancer.…”
Section: Discussionsupporting
confidence: 84%
“…Further attesting to gallstones being a risk factor for gallbladder carcinoma, the incidence of this cancer rises when the cholecystectomy rate declines 184,195. Nevertheless, consensus does not generally favor prophylactic cholecystectomy for asymptomatic stones196,197 as cholelithiasis is too common and gallbladder cancer too rare. Potential exceptions include large stones greater than 3 cm, which have a risk of 4% over 20 years,27,198 and elderly American Indian females with gallstones 199…”
Section: Gallbladder Cancermentioning
confidence: 99%
“…The prevalence of gallstone increases with age; 2% with age of over 20 years, 20% over 40 years, and 30% over 70 [16]. Clinical course of asymptomatic gallstones suggests that 15-25% of patients develop biliary colic [17,18] and about 1-2% per year develop symptoms and need abdominal surgery for cholecystitis, obstructive jaundice, pancreatitis, and gallbladder cancer [19][20][21].…”
Section: The General Prevalence Of Gallstonesmentioning
confidence: 99%